Sport Clube União Torreense project: A carnival every 15 days - Melo, Jéssica Schepens Pires de (2021)
This Project A carnival every 15 days, within the Sports Marketing field, is about a sporting club in the city of Torres Vedras, Sport Clube União Torreense (SCUT). SCUT it’s a centenary club with a long tradition inside Portuguese football, and seen as a reference in this area, the “Oeste” (west) of Portugal. This study was born from a problem the club is facing nowadays, the low levels of presence of fans in the first team home games (men’s soccer team), and it fits in a new project the club is creating eyeing it’s medium/long term future – Torreense 2030. To overcome this problem, SCUT defined as a goal: attract local community to its stadium. With this in mind a concept based on the Torres Vedras Carnival was developed. This Carnival is a huge event within the city, recognized both in the country and internationally. The club wants to engage the community through the connection with the core values of this event, and with this, transfer the Carnival mood to its Stadium, transforming and enhancing the fans experience. After careful bibliographic studies, about Carnival, SCUT and Fandom, this work is mainly about testing these ideas within two focus groups: carnival organized groups and high school students from the city. Having investigate perceptions about this project, both attractive factors and limitations, the tests allowed us to form important conclusions about the project conditions, and in this way increase the success rate of its implementation.